То a problem of special terminology: the fine arts compound, a modern aesthetics - D.A. Plyako (Academy of Cognitive and Natural Sciences, 2006)
In the article analised the value of basic terms of fine art and their disparity to semantic maintenance of inlaind in them, and by similarly conducted the analysis of role and types of fine art in modern society.